ANALISIS BIBLIOMETRIK: DAMPAK TEKNOLOGI DALAM ISLAMIC BANKING PADA PENGUNGKAPAN CSR UNTUK KEBERLANJUTAN - Handayani, Puji; Asfiah, Nurul (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2025)
This bibliometric analysis explores Islamic business ethics and corporate social responsibility (CSR) in the context of Islamic banking, as well as the practical implications and impacts of technology on sustainable development. The analysis of data collected from scientific publications between 2015 and 2024 shows a significant increasing trend in the number of publications and citations related to this theme. This study identifies three main clusters in the literature, namely Islamic business ethics, social responsibility, and technology in Islamic banking, which show an interconnected relationship in promoting sustainability. These findings emphasize the importance of adopting the latest technology in strengthening sustainable Islamic banking practices, as well as encouraging financial institutions to consider social, environmental, and Shariah-compliant aspects in their operations. Thus, this study provides guidance for academics and practitioners in developing insights and policies in a more inclusive and sustainable Islamic banking sector.